Southern African agriculture and climate change: A comprehensive analysis - South Africa - Johnston, Peter; Hachigonta, Sepo; Sibanda, Lindiwe M.; Thomas, Timothy S. (International Food Policy Research Institute, 2012)
This summary note is an excerpt from the chapter on South Africa that will appear in the peer-reviewed IFPRI monograph, Southern African Agriculture and Climate Change: A Comprehensive Analysis.